“The Only Feasible Means”: The Pentagon's Ambivalent Relationship with the Nuremberg Code - Moreno, Jonathan D. (The Hastings Center report, 1996)
Convinced that armed conflict with the Soviet Union was all but inevitable, that such conflict would involve unconventional atomic, biological, and chemical warfare, and that research with human subjects was essential to respond to the threat, in the early 1950s the U.S. Department of Defense promulgated a policy governing human experimentation based on the Nuremberg Code. Yet the policymaking process focused on the abstract issue of whether human experiments should go forward at all, ignoring the reality of humans subjects research already under way and leaving unanswered ethical questions about how to conduct such research. Documents newly released to the Advisory Committee on Human Radiation Experiments tell the story of the Pentagon policy.